2004
DOI: 10.1099/jmm.0.05453-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial-resistance and enterotoxin-encoding genes among staphylococci isolated from expressed human breast milk

Abstract: Resistance traits and the presence of enterotoxin-encoding genes were investigated in staphylococcus isolates obtained from expressed human breast milk. A total of 54 staphylococcal isolates identified as Staphylococcus epidermidis (53 . 6 %), Staphylococcus warneri (20 . 4 %), Staphylococcus haemolyticus (13 %) and Staphylococcus aureus (13 %) were investigated. By using a disc-diffusion method, higher rates of resistance, including intermediate resistance, were observed for penicillin (87 %) and erythromycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…Staph aureus was sensitive to all the antibiotics tested. This agrees with the work of [56], who reported that Staph aureus was 100% sensitive to gentamycin and cephalosporins, but disagrees with the work of [57] who observed the resistance of Staph auerus to penicillin and erythromycin. Pseudomonas aeruginosa was resistant to all the antibiotics tested (Tables 1(a)-(d)).…”
Section: Discussioncontrasting
confidence: 50%
“…Staph aureus was sensitive to all the antibiotics tested. This agrees with the work of [56], who reported that Staph aureus was 100% sensitive to gentamycin and cephalosporins, but disagrees with the work of [57] who observed the resistance of Staph auerus to penicillin and erythromycin. Pseudomonas aeruginosa was resistant to all the antibiotics tested (Tables 1(a)-(d)).…”
Section: Discussioncontrasting
confidence: 50%
“…In our study, the only independent difference between BMCR and formula was a greater mucosal colonization by S. haemolyticus in the formula-than in the BMCR-fed babies. This finding is not surprising because S. haemolyticus is almost never found in breast milk [42,43] and is likely acquired from the hospital environment rather than from breast milk, similar to most other microorganisms [6]. The ability of breast milk feeding to reduce bloodstream infections caused by S. haemolyticus is less clear.…”
Section: Discussionmentioning
confidence: 71%
“…None of the S. aureus isolated in this work carried more than one AME gene. Other similar studies reported aac(6')/ aph (2'') as the most frequently detected AME gene (83%) among S. aureus isolates [24,25]. Some studies reported a prevalence of the three AME genes in 21% of isolates [26].…”
Section: Discussionmentioning
confidence: 92%